Influence of cover crops with allelopathic potential and their reduction of herbicide use for soybean productivity. Issue 11 (2nd November 2022) - Bianchini, Alexandre; Dutra de Moraes, Pedro Valério; Domanski Jakubski, Juliana; Adami, Paulo Fernando; Bernardi Rankrape, Cristiana; Rossi, Patricia
Abstract: The allelophaty expressed by soil cover crops over weed varies according to species, quality and quantity of material produced. The purpose of this study was to evaluate the potential of cover crops and in the management of weeds and their effects on soybean yield. The experiment was laid in tri-factorial randomized block design with four replication. Factor A was cover crops (oats, forage chicory, quinoa and fallow), factor B was application of paraquat 400 g i.a ha −1, glyphosate 1200 g i.a ha −1 and mowing and factor C was one and two applications of post-emergent herbicide (glyphosate). For cover crops, the percentage of soil cover was evaluated at 53 DAE (days after emergence) of soybean. Weed species and their densities at 53 DAE of soybean were identified. At the end of the experiment, soybean yield was evaluated. The data were analyzed by the F test and comparison between means by the Tukey test ( P ≤ 0.05). Oats are the best option for weed inhibition and early soybean development. Quinoa and forage chicory were slow to cover the soil, but weed inhibition occurred. There were no large variations in post-emergence herbicide applications, which made possible to reduce an application without compromising the expected result.